2016
DOI: 10.4149/213_150611n326
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of locally advanced pancreatic cancer by percutaneous and intraoperative irreversible electroporation: general hospital cancer center experience

Abstract: The aim of this study was to evaluate the safety of irreversible electroporation (ire) and the outcome of patients undergoing ire of locally advanced pancreatic cancer (Pc). twenty-one patients with unresectable Pc underwent open (n=19) or percutaneous (n=2) ire of the tumor using the Nanoknife system with two electrodes that were repositioned several times to affect the whole mass. The size of the tumor was 39±10mm with a range from 21 to 65mm. Five patients underwent neoadjuvant chemotherapy and seven patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Fourteen single arm studies were published regarding IRE for LAPC, either as margin accentuation [ 67 , 68 , 69 , 70 ] or as primary tumor treatment [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Patients were treated percutaneously [ 69 , 71 , 72 , 73 , 74 , 75 , 77 , 80 ], laparoscopically [ 70 ], or during laparotomy [ 68 , 69 , 70 , 72 , 73 , 76 , 78 , 79 ]. After a median follow-up of 1–29 months, the median OS from diagnosis ranged between 15.3 and 27.0 months [ 68 , 70 , 74 , 75 , 76 , 77 , 78 ], whilst the median OS from IRE varied between 7.0 months and 14.2 months [ 67 , 73 , 74 , 75 , 77 , 81 ].…”
Section: Irreversible Electroporation (Ire)mentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen single arm studies were published regarding IRE for LAPC, either as margin accentuation [ 67 , 68 , 69 , 70 ] or as primary tumor treatment [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Patients were treated percutaneously [ 69 , 71 , 72 , 73 , 74 , 75 , 77 , 80 ], laparoscopically [ 70 ], or during laparotomy [ 68 , 69 , 70 , 72 , 73 , 76 , 78 , 79 ]. After a median follow-up of 1–29 months, the median OS from diagnosis ranged between 15.3 and 27.0 months [ 68 , 70 , 74 , 75 , 76 , 77 , 78 ], whilst the median OS from IRE varied between 7.0 months and 14.2 months [ 67 , 73 , 74 , 75 , 77 , 81 ].…”
Section: Irreversible Electroporation (Ire)mentioning
confidence: 99%
“…Patients were treated percutaneously [ 69 , 71 , 72 , 73 , 74 , 75 , 77 , 80 ], laparoscopically [ 70 ], or during laparotomy [ 68 , 69 , 70 , 72 , 73 , 76 , 78 , 79 ]. After a median follow-up of 1–29 months, the median OS from diagnosis ranged between 15.3 and 27.0 months [ 68 , 70 , 74 , 75 , 76 , 77 , 78 ], whilst the median OS from IRE varied between 7.0 months and 14.2 months [ 67 , 73 , 74 , 75 , 77 , 81 ]. In the study from Martin et al, the difference in OS between patients treated with IRE for primary tumor control (median OS: 23.2 months) was compared to IRE as margin accentuation after resection (median OS: 28.3 months).…”
Section: Irreversible Electroporation (Ire)mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In the meta-analyses by Ansari et al, 8 there were a total of 9 mortalities in 446 patients (2%). Severe complication rate was reported to be between 0 and 24%, 17,18 while minor complication rate ranged from 10 to 62%. 12,19 In the largest experience of 200 patients published by Martin et al, 9 20 (40%) of the resected patients and 54 (36%) of the nonresected patients experienced a total of 49 and 100 complications, respectively.…”
Section: Complicationsmentioning
confidence: 99%
“…Lambert et al showed that although intraoperative IRE does not result in improved overall survival, it can ameliorate the quality of life (Karnofsky score). Therefore, electroporation constitutes a safe palliative treatment option for patients with unresectable tumours [ 69 ].…”
Section: Irreversible Electroporation (Ire)mentioning
confidence: 99%